The factors influencing the academic staff of training effectiveness at KUIM / Rofiza Ibrahim - Ibrahim, Rofiza (2010)
Today’s organizations have realized the importance of training. Therefore, training programs are planned and managed carefully to ensure that employees who have received the training will be able to apply what they have learned and increase their work performances. The HR manager must really outline the required training programs that focus to the outcomes as well as measure the effectiveness of the training. Factors that contribute to the training effectiveness must be put into serious consideration so that the amount invested into training is benefited. As such, the objectives of this paper are to review and reveal the factors that influence the training effectiveness of academic staff in Kolej Universiti Islam Melaka. The result of this research revealed that most of the factors discussed have an impact to the training effectiveness. The study finds that training effectiveness is positively correlated with training program, participant, organization and also working environment variable both training program and organization have a relationship in influencing training effectiveness of the academic staff of Kolej Universiti Islam Melaka. It also provides an answer to top management to ensure all factors are well taken care so that suitable actions plan can be taken to improve training effectiveness.